The Role of QMS in Improving the Efficiency of Academic Information Systems - Muchdar Daeng Patabo; Aurelio Jansen Pontoh; Nadia Salsabilah Soleman; Keren Hapuk Kontey; Angel Rira (Cerdika: Jurnal Ilmiah Indonesia, 2026)
The purpose of writing this journal is to analyze the role of the Quality Management System (QMS) in improving the effectiveness of academic information systems in higher education. Currently, academic information systems have become one of the key factors in supporting educational processes, ranging from student data management to academic administration; however, many institutions still encounter issues such as invalid data and slow processes. By implementing QMS, institutions are expected to apply quality standards that meet established requirements. In this study, a descriptive qualitative method was used with a narrative analysis technique, focusing on the application of ISO 9001 as the QMS standard. The results of the analysis indicate that consistent implementation of QMS can significantly improve the efficiency of academic information systems, both in terms of service speed and data accuracy. This analysis concludes that the integration of QMS, particularly ISO 9001-based systems, is an essential strategy for higher education institutions in establishing effective, efficient, and sustainable academic information systems.